Liikunnanopettajan asiantuntijuuden kehittäminen: Reflektoiden, rinnakkain ja rajallisesti - Kukkonen, Riina; Saari, Essi (2025)
Saari, E. & Kukkonen, R. 2025. Development of Physical Education Teachers' Expertise: Reflectively, in Parallel and Within Constraints. Faculty of Sport and Health Sciences. University of Jyväskylä, Master's Thesis in Sport Pedagogy, 54 pages, 5 appendices.